Why we are not satisfied: in the context of declining factors of ummah - U Tun Aung, Maulana Akbar Shah (University Sains Islam Malaysia, 2015)
The question "Why we (Muslims) are not satisfied?" is known to everyone that our desires are not fulfilled in ways that we willed to be. Then another additional question that comes up is that how to fulfill those desires? An answer from the Islamic perspective is that we ignore the principles of Qur’anic values. The 21st century has been the most challenging period for the Muslim Ummah as we are confronted with many undesirable challenges, wherever we go. These challenges seem beyond our understanding and capability. Ultimately, we fail to tackle these challenges resulting obsolete and branded as fundamentalists, extremists or terrorists. As a matter of fact, we were capable in every area of administration, politics, economics, education; science and technology by which we had built our golden age of Islamic civilization in the past. Now, all those bounties, facilities and glories had been a dream and were taken away. Scholars suggested that the reason for our failure is that we were corrupted and had ignored the values of Al Quran and Sunna. This paper is trying to identify the reason of failure of the Ummah and providing suggestions to find reviving their misplaced glory, built up by their forefathers in the past and restoring their misguided souls.